Study on the effect of self-hypnosis in reducing exam anxiety - Vidya, Bhagat; Sheila, Menon (2019)
Exam anxiety can impact on a student’s ability to cope in both negative and positive ways. It is normal for students facing examinations to experience anxiety known as exam anxiety. It is also true that over anxiousness disregulates their homeostasis at physical, emotional, and cognitive levels which can result in poor examination performance. The current study has analyzed past reviews regarding test anxiety and its impact on students’’ performance in their examinations. The purpose of the study is to develop an awareness of the benefits which self-hypnosis can bring in promoting a healthy anxiety response, which would benefit students in coping with their exams. A literature review was completed using electronic databases for this study. The current study reviewed 30 articles from the year 1961 to 2018. The articles reviewed focused on test anxiety, positive and negative effects of anxiety on students, self-hypnosis and anxiety management. The study concludes that although test anxiety is common amongst students it has a positive effect on students in their preparatory stage. On the other hand, abnormal or over anxiousness negatively impacts on the students’ functional level, thereby affecting performance and achievement. The current study suggests that training students in self-hypnosis and the practicing of self-hypnosis would promote the overall health and wellbeing in student populations.